2000
DOI: 10.1021/es990618c
|View full text |Cite
|
Sign up to set email alerts
|

Distributed-Rate Model Analysis of 1,2-Dichlorobenzene Batch Sorption and Desorption Rates for Five Natural Sorbents

Abstract: Rate-limited sorption and desorption strongly influence the fate, transport, and remediation of organic pollutants in subsurface environments. In this study, the rates of sorption and desorption were quantified for 1,2-dichlorobenzene to and from five natural sorbents using a batch methodology. Solute/sorbent contact times of 3, 7, 14, 49, and 99 d were studied for the desorption rate experiments. The sorption and desorption data were simulated with a distributed-rate model that used the Γ probability density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 39 publications
0
44
0
Order By: Relevance
“…In the Forbes soil, this amount would presumably be smaller if the experiment were continued beyond 21 days due to nonattainment of apparent equilibrium. Very different initially adsorbed fractions (for sorption times Ͻ 1 h) were observed previously: Ball and Roberts (1991b) found ϳ4-25%, Weber and Huang (1996) found ϳ10-15%, and Deitsch et al (2000) found ϳ25-60%. Common to these observations is that the smaller the initial adsorbed amount, the longer the apparent equilibration time, in agreement with the observations in this study.…”
Section: Resultsmentioning
confidence: 42%
See 1 more Smart Citation
“…In the Forbes soil, this amount would presumably be smaller if the experiment were continued beyond 21 days due to nonattainment of apparent equilibrium. Very different initially adsorbed fractions (for sorption times Ͻ 1 h) were observed previously: Ball and Roberts (1991b) found ϳ4-25%, Weber and Huang (1996) found ϳ10-15%, and Deitsch et al (2000) found ϳ25-60%. Common to these observations is that the smaller the initial adsorbed amount, the longer the apparent equilibration time, in agreement with the observations in this study.…”
Section: Resultsmentioning
confidence: 42%
“…1d). Long and varying apparent equilibration times of sorption are a frequently observed phenomenon (e.g., Ball and Roberts, 1991b;Pignatello and Xing, 1996;Deitsch et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The research of Deitsch, Smith et al (2000) focuses on the rate limited sorption/desorption of an organic pollutant 1,2-Dichlorobenzene from 5 different soils.…”
Section: Component Additivity Methodologymentioning
confidence: 99%
“…An intraparticle diffusion model with parameters determined from uptake experiments was able to account for the majority of sorption hysteresis (Miller and Pedit 1992). Cunningham and Deitsch et al (2005) quantify sorption and desorption time scales for an organic contaminant onto four natural sorbents from the previous study above (Deitsch, Smith et al 2000) using temporal moment analysis. The authors develop a probability distribution by integrating the mean and variance of sorption and desorption time scales obtained from batch experimental data.…”
Section: Component Additivity Methodologymentioning
confidence: 99%
“…In the last few years new models have arisen. These models incorporate the possibility that sorption can be characterized by multiple rates at any single location, related to the presence of a nonuniform distribution of grain sizes [ Connaughton et al , 1993; Pedit and Miller , 1994; Culver et al , 1997; Cunningham and Roberts , 1998; Haggerty and Gorelick , 1998; Deitsch et al , 2000]. The most general model assumes a continuous distribution of mass transfer rates [ Haggerty and Gorelick , 1998] and was developed as an extension of various particular continuous and discrete models.…”
Section: Introductionmentioning
confidence: 99%